Estimating Psychosocial Risk Factors and Levels in Adolescents Attending School in Ambato, Ecuador - Moreta, Rodrigo; Reyes, Carlos; Mayorga, Marlon; León Tamayo, Lorena (Pensando Psicología, 2017)
Purpose: To determine the psychosocial risk levels in adolescents attending school in Ambato, Ecuador.Method: We worked with a group of 302 adolescents between 14-18 years old, from four educational institutions. The assessment was made through the Self-Description Inventory (SDI) for adolescents.Results: The results showed that the levels of risk behaviors and situations are below the cut-off point at all levels evaluated. Men exhibited greater differences (t(203)=3.094, p < 0.001) than women in the health risk dimension. We identified two vulnerable subgroups in the risk assessment: 20% of participants in the school dimension and 17% of women in the family dimension.Conclusions: Family and individual psychological history constitutes a risk factor that is present in more risk behaviors and situations. The scope of these results in future prevention and intervention plans with Ecuadorian adolescents is discussed.
Keywords: adolescents; schooling; prevention and intervention plans; risk situations